User Acceptance of Terms & Conditions and Privacy Policy: A Legal Analysis of the Position of Food Delivery Mobile Apps in the Malaysian Context - Karim, Mohammad Ershadul; Al Rezan, Mohammed Ibrahim; Hosain, Md. Mostafa (UUM Press, 2025)
Mobile applications, which are popularly known as ‘mobile apps’ are software applications generally used on wireless computing devices such as smartphones or tablets. Since tech giant Apple’s launch of the iPhone in 2007, these mobile apps are getting more attention across nations with the advancement of mobile internet, smartphone technologies, and navigational services. Food delivery mobile apps (FDAs) facilitate convenient and quick food delivery to customers and provide restaurants with better opportunities to generate more revenue without having to increase the seating capacities of their brick and-mortar outlets. Nevertheless, with these FDAs, users face a myriad of legal problems, including consent mechanisms and the acceptance of the terms and conditions (T&Cs) and privacy policies (PPs). These one-sided conditions warrant investigation from the perspective of consumer protection. This paper aims to uncover the T&Cs and PPs used in the FDAs popular in Malaysia from the perspective of consumer protection and privacy rights, based on the standards of contracts. By adopting a qualitative legal research methodology and analyzing primary and secondary literature, the research has developed several standards and grouped them under the headings of contract standards, contract changes and contract termination to evaluate the T&Cs and PPs of nine of the most popular FDAs in Malaysia. The study analysed the content of the T&Cs and PPs of these FDAs to explore whether they “comply”, “partially comply”, or “do not comply” with the standards developed. The study found that the FDAs failed to comply with these standards, highlighting legislative shortcomings that indicate a lack of supervision in app development processes and compliance. The paper concludes by offering recommendations for policymakers, which included increasing supervisory and monitoring capacity and reforming the relevant legal framework in the future. As the number of FDA users and the frequency of online food ordering have sharply risen in Malaysia, this study is highly relevant for examining the legal aspects, particularly regarding the T&Cs and PPs of these apps